The Impact of Seniority Culture and Senior Santri Behavior on Discipline and Moral Character in Pesantren - Muh Zaki Maulana; Misbahul Arifin; Ahmad Sahidah; Samira Agoro (Journal Of Social Siences And Islamic Studies (JOSIS), 2026)
This study aims to reveal the influence of seniors' behavior on discipline, learning motivation, and moral character of students at Nurul Jadid Islamic Boarding School. The main focus of this study is to analyze the interaction patterns of seniority in the daily life of students and their impact on the character development of younger students. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Informants consisted of foster guardians, pesantren administrators, and older and younger students. The results showed that the behavior of seniors who tended to be authoritarian and intimidating contributed to a decrease in discipline, learning motivation, and weakened the moral values of younger students. Although there are positive interactions, the frequency is very small compared to repressive interactions. This finding indicates that the culture of seniority that is applied excessively actually hinders the character education process in pesantren. The implications of this study emphasize the need to reformulate pesantren policies related to the pattern of relations between students with a more humanist and educational approach in order to create a coaching climate conducive to the moral and spiritual development of students.